Improved repair of rabbit calvarial defects with hydroxyapatite/chitosan/polycaprolactone composite scaffold-engrafted EPCs and BMSCs - Yu, Hedong; Xia, Lingyun; Leng, Xieyuan; Chen, Yongji; Zhang, Li; Ni, Xiaobing; Luo, Jie; Leng, Weidong (Frontiers in Bioengineering and Biotechnology, 2022)
Endothelial progenitor cells (EPCs) expressing vascular endothelial growth factor (VEGF) and platelet-derived growth factor (PDGF) and bone marrow mesenchymal stem cells (BMSCs) expressing endogenous bone morphogenetic protein-2 (BMP-2) play the important role in new bone formation. This study investigated the effects of a porous hydroxyapatite (HA)/chitosan (CS)/polycaprolactone (PCL) composite scaffold-engrafted EPCs and BMSCs on the expression of BMP-2, VEGF, and PDGF in the calvarial defect rabbit model in vivo. It showed that a three-dimensional composite scaffold was successfully constructed by physical interaction with a pore size of 250 μm. The HA/CS/PCL scaffold degraded slowly within 10 weeks and showed non-cytotoxicity. By X-ray, micro-CT examination, and H&E staining, compared with the HA/CS/PCL group, HA/CS/PCL + EPCs, HA/CS/PCL + BMSCs, and HA/CS/PCL + EPCs + BMSCs groups performed a more obvious repair effect, and the dual factor group presented particularly significant improvement on the percentages of bone volume at week 4 and week 8, with evident bone growth. Osteogenesis marker (BMP-2) and vascularization marker (VEGF and PDGF) expression in the dual factor group were much better than those of the HA/CS/PCL control group and single factor groups. Collectively, the HA/CS/PCL composite scaffold-engrafting EPCs and BMSCs is effective to repair calvarial defects by regulating endogenous expression of BMP-2, VEGF, and PDGF. Thus, this study provides important implications for the potential clinical application of biomaterial composite scaffold-engrafted engineering cells.